2018
DOI: 10.4103/ijnmr.ijnmr_158_16
|View full text |Cite
|
Sign up to set email alerts
|

Health journalism: Health reporting status and challenges

Abstract: Background:Media play crucial role in disseminating health information. Due to the importance of accurate health news reports, and the national need to professionalism in health journalism, this study aimed to investigate the characteristics of health journalists, and health reporting status and the challenges involved.Materials and Methods:Using consensus sampling, this descriptive cross-sectional study was conducted on all health news reporters in Isfahan (34 journalists) in 2015–2016. Data collection was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Previous studies have identified that many health journalists lack the training required to accurately disseminate health news, leading to potentially harmful health effects. 70 71 The low scores across all tools indicate overall inadequacy of both reliability and accuracy. A survey of medical journalists across 37 countries highlighted the 3 most common barriers against quality content: lack of time, space and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that many health journalists lack the training required to accurately disseminate health news, leading to potentially harmful health effects. 70 71 The low scores across all tools indicate overall inadequacy of both reliability and accuracy. A survey of medical journalists across 37 countries highlighted the 3 most common barriers against quality content: lack of time, space and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Health reporting has been found to be low on the priority of publishers, therefore, their commitment to building capacity in this area also has been limited. 2 , 14 , 15 The journalists lack the necessary specialized training when dealing with the intricacies of health news. 2 , 15 As a result, their capacity to report health news about different diseases has low precision and high sensation.…”
Section: Discussionmentioning
confidence: 99%
“…The public is educated by the media to survive during a pandemic. The media is a funnel of information from the government, health experts, and policymakers to the public regarding health management (Keshvari, Yamani, Adibi, & Shahnazi, 2018). The media can educate the public to manage risk and encourage integrated and synergistic problem handling (Budi HH, 2012).…”
Section: Empathymentioning
confidence: 99%
“…Furthermore, they avoid speculation and personal interpretation as much as possible in providing health information. Accurate and in-depth information is strength in health care (Keshvari et al, 2018). Although the speed of information is a mainstay for online media in sharing information, in the context of health, the completeness and accuracy of information accompanied by verification is strength in health journalism.…”
Section: Empathymentioning
confidence: 99%